P076 Five years of feedback for the newly diagnosed course – an evaluation of a peer-led intervention for people diagnosed with HIV. (8th June 2017) - Oxenham, Chantal; Haddow, Lewis; Sandulescu, Cristian; Bayakwaga, Angela; Sandford, Christopher; Sultan, Binta; Williams, Ian; Waters, Laura; Edwards, Simon; Tariq, Shema
Abstract : Introduction: New diagnosis of HIV can be psychologically challenging, and presents an important opportunity to improve health literacy and engagement in care. Peer-led interventions are an effective means of providing support to people living with HIV (PLWH). We present an evaluation of a newly-diagnosed course (NDC) in London. Method: The NDC, established in its current form in 2011, is accessible to 'those recently diagnosed or struggling with diagnosis'. Providing a structured, peer-led, group-based, participatory programme delivered by experienced facilitators. NDC comprises 6 sessions (21 contact hours). All participants were invited to complete pre-and post-course questionnaires (using a 4-or 5-point scale), most did at the first and last sessions. This analysis presents data from 2011-2016. Data were analysed in STATA using Wilcoxon signed rank test. Results: Across 30 NDCs, 314 participants completed both questionnaires (response rate 87%). The majority were men who have sex with men (91.3%), 72% of whom were of white ethnicity. Approximately 15% were female, the majority Black-African ethnicity (56%) and heterosexual (88%). Heterosexual men and transgender individuals represented 6.5% and 0.3% respectively. The table summarises participant's responses for selected questions (P Values <0.001 for all comparisons): Discussion: This innovated peer-led NDC engaged over 300 PLWH since 2011, resulting in short-term self-reported improvements. 6-and 12-month questionnaires would assess durability of changes, and we're exploring the association with attendance at NDC and clinical outcomes (e.g. viral suppression and retention in care). In conclusion, the NDC is a sustainable and acceptable model, providing holistic support and promoting self-management in PLWH.